Pengaruh Pelatihan Pegawai Berkala terhadap Perubahan Perilaku Organisasi dalam Lingkungan Institusi Pendidikan di Medan - Elfrida Yanti Simanjuntak; Jefri Harefa; Andi Berkat Zamasi; Adriel Hutagalung; Viona Ameyliasari Waruwu; Cerah Damayanti Lase; Faerizaro Zalukhu; Ririntia Justriany Pandiangan; Putriani Halawa; Maduma Sari Sagala (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This research is motivated by the phenomenon of changes in organizational behavior which is considered less than optimal, especially in the environment of educational institutions in the city of Medan. In the dynamics of daily work, various challenges are still found such as low levels of discipline, weak work initiatives, and lack of collaboration and professionalism among educators and education staff. One of the factors that is suspected to be the main cause of these problems is irregularities in the implementation of training or human resource capacity development. Training should be a strategic means of instilling organizational values, building a positive work culture, and improving individual and collective competencies. Training that is designed and implemented periodically is believed to be able to be one of the important instruments in changing the work behavior of educational apparatus towards a more productive and professional direction. However, in practice, there have not been many studies that have empirically tested the extent to which periodic training is able to influence real changes in organizational behavior. Therefore, this study aims to quantitatively examine the effect of periodic training on organizational behavior changes in educational institutions, especially in the city of Medan. The main focus of this study includes three important aspects, namely improving work culture, increasing collaboration among others, and increasing professionalism. Data was obtained through survey techniques on a number of respondents from various educational institutions. The results of the study show that periodic training makes a significant contribution to improving discipline, work initiative, a sense of responsibility, and forming a pattern of work behavior that is adaptive to organizational changes and challenges.